Lacrimal bone cyst : a case report - Che Mohamed, Siti Kamariah; Yunus, Rohaizan; AK, Shamin (Universiti Sains Malaysia, 2007)
Bone cyst is a rare benign bone tumour which normally affect the vertebral region or long bones. Despite its benign in nature, this lesion is expansile and may cause local compression and destruction of bones and soft tissues. Involvement of facial bones is very uncommon, and the lacrimal bone is very rare. Diagnosis usually achieved by radiological investigations, operative findings, and confirmed by histopathological findings.